Kendala Membangkitkan Pariwisata Pasca Pandemi di Kabupaten Belitung Timur - Fadillah Dilla; EW Tri Nugroho (SOSIO PROGRESIF | Media Pemikiran Studi Pembangunan Sosial, 2022)
The impact of the Corona Virus Disease 2019 (COVID-19) pandemic has paralyzed the tourism sector in East Belitung Regency. It can be seen from the number of tourist visits that have fallen drastically, as well as indicators of the decline in hotel occupancy rates on Belitong Island. Tourism activities that support the triumph of tourism were not carried out due to the Covid-19 pandemic which required the Regional Government to issue a policy of limiting community activities. In addition, refocusing the budget for cultural and tourism activities so that these activities are not carried out. The Department of Culture and Tourism seeks to stimulate tourism in East Belitung post-covid-19, by increasing tourist attraction objects through making tour packages at leading tourist attractions, conducting tourism promotions. Improving the accessibility of sea transportation by providing glass-floored vessels, increasing amenity by conducting educational socialization of guest reception SOPs for hotel employees in order to increase hotel occupancy, improve infrastructure facilities in tourist destinations, as well as improve coordination and facilitate tourism institutions. This study describes the obstacles faced by the Department of Culture and Tourism in generating tourism after the COVID-19 pandemic, with a qualitative-descriptive approach. Data were collected through observation, interviews and documentation. The data analysis technique starts from data reduction, data presentation and conclusion drawing. The results of this study indicate that hotel occupancy rates are still low in East Belitung, do not have public transportation to support tourism, human resources are less able to manage tourism potential, dependence on tin mining.